2018
DOI: 10.3791/57615
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow Input Genome Sequencing Library Preparation from a Single Tardigrade Specimen

Abstract: Tardigrades are microscopic animals that enter an ametabolic state called anhydrobiosis when facing desiccation and can return to their original state when water is supplied. The genomic sequencing of microscopic animals such as tardigrades risks bacterial contamination that sometimes leads to erroneous interpretations, for example, regarding the extent of horizontal gene transfer in these animals. Here, we provide an ultralow input method to sequence the genome of the tardigrade, Hypsibius dujardini, from a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The steady development of sequencing technologies is allowing the generation of genomes spanning the diversity of life, which now includes minute organisms. Indeed, thanks to the latest low and ultra-low DNA input protocols, sequencing high-quality genomes from millimetric animals is now possible ( Yoshida et al, 2018 ; Schneider et al, 2021 ; Lord et al, 2023 ). In this study, we used the Pacbio Ultra-Low DNA Input protocol to sequence the genome of N. westbladi , reporting the first nemertodermatid genome, sequenced from a single microscopic worm.…”
Section: Discussionmentioning
confidence: 99%
“…The steady development of sequencing technologies is allowing the generation of genomes spanning the diversity of life, which now includes minute organisms. Indeed, thanks to the latest low and ultra-low DNA input protocols, sequencing high-quality genomes from millimetric animals is now possible ( Yoshida et al, 2018 ; Schneider et al, 2021 ; Lord et al, 2023 ). In this study, we used the Pacbio Ultra-Low DNA Input protocol to sequence the genome of N. westbladi , reporting the first nemertodermatid genome, sequenced from a single microscopic worm.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, no sustainable culture of heterotardigrades has been established to date. Therefore, we employed an ultra-low-input genome sequencing protocol that we developed previously [38][39][40] to achieve whole genome sequencing from a single specimen of tardigrade containing less than 50 pg of DNA collected from the wild. However, such a sample requires strong precautions to minimize the possibility of contamination 23,38,42 .…”
Section: Discussionmentioning
confidence: 99%
“…We used the ultra-low-input library sequencing protocol established in our previous study 39,40 . In brief, genomic DNA was extracted using a Quick-gDNA Microprep Kit (Zymo Research) after lysis with two freeze-thaw cycles of -80°C and 37°C incubation, and the extracted DNA was sheared to 550-bp target fragments with Covaris M220.…”
Section: Genome and Transcriptome Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that used H. exemplaris strain Z151 prior to the 2018 species disambiguation from H. dujardini (Gasiorek et al 2018) generally referred to the species as H. dujardini, or as Hypsibius cf. dujardini, and in many of these studies the strain was indicated as Z151 and/or sourced from Sciento Bavan et al 2009;Mali et al 2010;Cesari et al 2012;Beltrán-Pardo et al 2013;Horikawa et al 2013;Tenlen et al 2013;Smith and Jockusch 2014;Boothby et al 2015Boothby et al , 2017Gross and Mayer 2015;Kondo et al 2015;Arakawa et al 2016;Bemm et al 2016;Fernandez et al 2016;Hering et al 2016;Hyra et al 2016a,b;Kosztyła et al 2016;Koutsovoulos et al 2016;Levin et al 2016;Smith et al 2016Stec et al 2016;Erdmann et al 2017;Gross et al 2017Gross et al , 2018Vasanthan et al 2017;Yoshida et al 2017Yoshida et al , 2018Fadero et al 2018;Nelson 2018;Rost-Roszkowska et al 2018). One study using Thulinia stephaniae (Hejnol and Schnabel 2005) indicates some contrasting developmental features in a second tardigrade species.…”
Section: Related Speciesmentioning
confidence: 99%